Aspek Ushul Fiqih Dalam Tafsir Al Qurthubi: Studi Analisis Q.S. An Nur: 31 - Cholid Ma'arif (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Tafseer Jami ' al-Ahkam or commonly known as Tafseer Qurtubi by Shaykh al-Qurtubi The origin of Cordova (d. 671 AD) is one of the classical interpretations that dentists the orientation of the law in its interpretation pattern. However, in the application of drafting his Tafseer he was not only carried over in the flow, but also quoted various verses, Hadith prophets, and other Qur'anic texts as a reasonable effort. Starting from the assumption that the science of interpretation is based on the rule of Usul Fiqh in its development, then the author seeks to uncover the nuances of the Islamic jurisprudence in the interpretation of Al Qurtubi. For this purpose, the writing of this article is directed at a library of descriptive-analytical methods of analysis by making QS. Al-Nur as the object of Formanya and Tafsir Al Qurthubi himself as the object of the material. The study in this verse resulted in the tracking of the Fiqh jurisprudence especially the aspect of the Istihsan or the Istishlah Malikiy to read the tendency Al Qurthubi to calculate the use of Cadar. Where while the parties make the interpretation of the same as the conclusion of the veil, although actually the meaning of the birth of the verse is concerned with the care of views, closing the jewelry, and the traditional story of the habit of Arab society in hooded. This was used by Maliki's fiqh readings, beginning with three maqashid levels to the application of its interpretation.